Photodynamic therapy in endodontics: literature review. - Faria Damasceno , Maria Cleyde; do Carmo Araújo , Maria Madalena (Brazilian Journal of Implantology and Health Sciences, 2021)
Endodontic therapy seeks to prevent and when necessary to eliminate endodontic infections. The persistence of microorganisms to the mechanical chemical preparation or the intracanal medication is considered the main cause of the failures of the endodontic treatment. In these cases Enterococcus faecalis is the most commonly found microorganism. Photodynamic therapy (PDT) emerges as a promising adjuvant therapy to conventional endodontic treatment to eliminate these persistent microorganisms. This therapy consists in the association of a specific light source with a photosensitizer in the presence of oxygen, producing cytotoxic species to the microorganisms. Thus, the present article aims at a review of the literature on the use of photodynamic therapy in endodontics, a test that is shown to assist in the preparation of the root canal.